Linear ARX modelling of pneumatic actuator system - Khong, F. H.; Rahmat, M. F.; Sunar, N. H.; Ramli, Mimi Faisyalini; Jamaluddin, Juliza; Ahmad, Nasarudin; Nawawi, Sophan Wahyudi; Ibrahim, Sallehudin; Md. Yunos, Yusri (Penerbit UTHM, 2022)
Pneumatic actuator system refers to a series of pneumatic sourced interconnected components (includes pneumatic actuator) that results in mechanical movement when operated. Pneumatic actuator system is commonly found in manufacturing and automation industries to execute high frequency and repetitive mechanical motion (linear or rotary). Comparing to electrical and hydraulic actuator system, the pneumatic actuator system possesses some absolute advantage, such as providing greener, cleaner and fail-safe environment (oil/spark free), and lower cost in operation and maintenance. Due to these advantages, the pneumatic actuator system gradually become the standard solution in industry by replacing electrical actuator system. The modelling of pneumatic actuator system can be done by either analytical method [1] [2] [3] or empirical method [4] [5] [6]. Both of the method has their own advantages. However, the pneumatic actuator system is not a singular body system, it consists of several interconnected components such as proportional control valve, pneumatic cylinder, and sensors. Due to this reason, the empirical approach could be the solution in modelling the system, as analytical method is complicated and exhausting, although nonlinearity is ignored as an assumption in modelling.